Cyclopentane as an Eco-Friendly Alternative: A Review of its Properties, Industrial Applications, and Production Methods - Filina, M.P.; Bakibaev, A.A.; Baiguzin, F.A. (Eurasian Journal of Chemistry, 2025)
The Montreal Protocol established stringent international regulations concerning the production, consumption, and trade of ozone-depleting substances, including chlorofluorocarbons and hydrofluorocarbons, aimed at safeguarding the Earth’s ozone layer. In this context, cyclopentane has emerged as an environmentally sustainable alternative owing to its zero-ozone depletion potential and low global warming potential. This review examines the physicochemical properties, industrial applications, and production methods of cyclopentane, with particular emphasis on its utilization as a refrigerant, a blowing agent in rigid polyurethane foams, and a hydrate-forming agent for seawater desalination. The primary applications are concentrated in refrigeration and thermal insulation, where cyclopentane-based foams demonstrate superior thermal conductivity and mechanical stability relative to conventional agents. However, the flammability of cyclopentane vapor presents operational challenges that necessitate the implementation of appropriate safety measures. Advances in catalytic reaction-distillation and extractive distillation processes may improve the efficiency of cyclopentane production and product purity in industrial settings. This review underscores cyclopentane’s efficacy as a substitute for compounds with higher ozone depletion potentials and emphasizes the importance of ongoing research into scalable, economically viable production technologies and safe industrial integration to fully realize its environmental and practical benefits.
Keywords: cyclopentane; fraction C5; pyrolysis; cyclopentene; cyclopentadiene; hydrogenation; cyclopentane hydrates; eco-friendly